Cigarette smoke regulates the expression of TLR4 and IL-8 production by human macrophages - Rahman Irfan; Kraneveld Aletta D; Karimi Khalil; Mortaz Esmaeil; Sarir Hadi; Caldenhoven Eric; Nijkamp Frans P; Folkerts Gert (BMC, 2009)
Abstract Background Toll-like receptors (TLRs) are present on monocytes and alveolar macrophages that form the first line of defense against inhaled particles. The importance of those cells in the pathophysiology of chronic obstructive pulmonary disease (COPD) has well been documented. Cigarette smoke contains high concentration of oxidants which can stimulate immune cells to produce reactive oxygen species, cytokines and chemokines. Methods In this study, we evaluated the effects of cigarette smoke medium (CSM) on TLR4 expression and interleukin (IL)-8 production by human macrophages investigating the involvement of ROS. Results and Discussion TLR4 surface expression was downregulated on short term exposure (1 h) of CSM. The downregulation could be explained by internalization of the TLR4 and the upregulation by an increase in TLR4 mRNA. IL-8 mRNA and protein were also increased by CSM. CSM stimulation increased intracellular ROS-production and decreased glutathione (GSH) levels. The modulation of TLR4 mRNA and surface receptors expression, IRAK activation, IκB-α degradation, IL-8 mRNA and protein, GSH depletion and ROS production were all prevented by antioxidants such as N-acetyl-L-cysteine (NAC). Conclusion TLR4 may be involved in the pathogenesis of lung emphysema and oxidative stress and seems to be a crucial contributor in lung inflammation.